EP1008 Modified posterior exenteration in advanced ovarian cancer: a single center experience. (1st November 2019) - Papanikolaou, A; Tsolakidis, D; Pappas, P; Zouzoulas, D; Pitis, S; Theodoulidis, V; Grimbizis, G
Abstract : Introduction/Background: Modified posterior exenteration is frequently a necessity in order to accomplish complete cytoreduction in advanced ovarian cancer patients with extensive intra- peritoneal dissemination. The aim of this study is to present the characteristics of patients experiencing bowel resection and to analyse the surgical outcomes and complications after debulking surgery in a tertiary gynecological center for ovarian cancer. Methodology: Medical records of 79 patients with ovarian cancer who underwent bowel resection between January 2004 and December 2018 retrospectively reviewed. Complications, cytoreductive and oncological outcomes were reported. Results: 51 (64.5%) patients underwent bowel resection during primary, 17 (21.5%) during interval and 11 (13.9%) during secondary debulking surgery. Intestinal surgeries included: 47 patients underwent rectosigmoid resection, 9 had colectomy and 6 had colectomy plus rectosigmoid resection. From the rest patients 9 underwent small bowel resections and 8 multiple enterectomies. Complete and optimal (<1 cm) debulking was achieved in 44 (55.7%) and 27 (34.1%), respectively. Median hospitalization was 10 days. Median perioperative blood loss was 600cc and postoperative blood transfusion was mandatory in 43 patients. Median resuscitation time was 4 hours and 25 (31.6%) patients required ICU admission after surgery. Postoperative complications such as pelvic abscess formation were observed in 3 patients and fistula in one of them. Median disease-free and overall survival was 25 and 42 months, respectively. Perioperative mortality was 3.9%. Conclusion: Modified posterior exenteration is the most frequent additional procedure in order to achieve complete or optimal cytoreduction in advanced ovarian cancer. It has acceptable perioperative morbidity, mortality and increased survival rates. Disclosure: Nothing to disclose.